PEMFC Flow‐field Design, Channel/land Width Ratio Optimization. Issue 3 (3rd March 2020) - André, J.; Claude, E.; Sirac, D.; Gastaldin, D.; Rossinot, E.
Abstract: The impact of different land width and channel span configurations was evaluated on a 260 cm 2 active area short stack. Polarization curves were compared at 65 °C cell output, max 7 °C cell delta T, 50% RH humidified air, ambient pressure at cell outlet, air pressure drop below 4 kPa at 1 A cm −2 . Adequate opening ratio, about 50% or more is widely recognized as an optimal value to minimize contact resistance and diffusion losses at high current density. However, this work tends to show that performance optimization is linked to the total channel edge length per centimeter squared, ponderated by the opening ratio value. Total channel edge length is simply the sum of the edge length values on the flow‐field in contact with the membrane electrode assembly (MEA). Edges actually concentrate all the conditions for the reaction to occur: presence of gas phase and easy electron transport thanks to plate bulk conductivity. This could explain contrasted results existing in literature. Based on this work, a new cell design was developed allowing to reach 1 W cm −2 (extrapolated) with less than 20 kPa pressure drop (i.e., unchanged operating conditions except that pressure drop reached 10 kPa due to shallower channels compared to base case).